The case for rigorous comparative research and population impacts in a new era of evidence-based interventions for juvenile offenders - Welsh, Brandon (Criminology & public policy, 2020)
A key take away from Elliott et al.’s critical review is the need for a program of more rigorous comparative research to assess the two main evidence-based models for guiding juvenile justice interventions. Additionally, a sound measure of this research should be whether or not the different models are able to achieve (and sustain) population impacts. Both of these are important issues facing the evidence-based movement in juvenile justice today, and the purpose of this essay is to make the case for greater attention to each one. The decision-tree method and computer simulation modeling represent two rigorous approaches, and their use could benefit immensely understanding of the comparative effectiveness of the different models. It will also be important to consider other existing models as part of a program of comparative research. The risk-need-responsivity model and Communities That Care are two examples. A key criticism of evidence-based interventions, whether they are brand-name programs or generic practices, is the limited research demonstrating their ability to achieve population impacts. Some of the views undergirding this criticism are warranted. At the same time, advancements in the science of implementation over the last two decades bolster support for scaling up evidence-based interventions and attaining impacts at the population level. Efforts underway in several states provide additional support for the ability to scale-up evidence-based juvenile justice interventions and achieve population impacts. Expanding the scope and accelerating the pace of this work begins by building on the progress so far as well as a renewed political will.